THE EFFECT OF TRANSFORMATIONAL AND TRANSACTIONAL LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS INTERVENING VARIABLE - Asman Tayo; Mia Syafrina; Adhitomo Wirawan (Politeknik Negeri Batam, 2022)
This study explores the effect of transformative transactional leadership style on employee performance, with work motivation as an intervening variable. The respondents of this survey were the population of the Riau Islands National Narcotics Agency, which amounted to 68 respondents. Using the sampling method is intended by the sampling method. In this survey, data is collected through a survey in the form of Google Forms. Descriptive and route analysis were used as data analysis techniques. The results of the three independent variables are 1. The transformational leadership style variable has a positive and important effect on work motivation. 2 The transaction leadership style variable has a significant negative effect on work motivation. 3. The transformational leadership style variable has a positive and significant effect on employee performance. 4. Transactional leadership style variable has a negative effect on employee performance. 5. Fluctuating work motivation has a positive and significant effect on employee performance